The Influence of Social Media Marketing on Purchase Intentions with Brand Trust and Brand Image as a mediating role in Avoskin Products - Fakriyah, Icha Putri; Agus Abdurrahman (MultiTech Publisher, 2024)
This research aims to test and analyze the influence of social media marketing on intention to purchase Avoskin products with brand trust and brand image as mediating roles. The population of this research is Avoskin product users in Generation Z who live in the Special Region of Yogyakarta. This research used a purposive sampling method. Testing in this research used SPSS software, and SEM analysis used the SmartPLS application. The results obtained from testing in this research indicate that brand trust has a positive influence in mediating the relationship between social media marketing and purchase intentions. In addition, brand image has a positive influence in mediating the relationship between social media marketing and purchase intention. However, social media marketing hurts purchase intentions.